Activities of Brain Gymnastics Against Enhancement of Cognitive Function in the Elderly - Priyanto, Kurniawan Edi; Sumardiyono, Sumardiyono (Universitas STRADA Indonesia, 2021)
Background: The old age is a period that cannot be avoided by anyone, especially for those who are endowed with long life, which can be done by humans is only to prevent the aging process so that it is not too fast, because in essence the aging process occurs a setback. or decrease. One of them is a decline in cognitive function, cognitive decline in the elderly can include various aspects, namely orientation, registration, attention, and calculations, memory and language. The problem of this research is the decline in cognitive function in the elderly can cause problems including long memory and information processing, in the long memory of the elderly it will be difficult to reveal new information or stories or events that are not so interesting. Methods: The design in this study uses Quasi Experimental with Non Randomized Control Group Pre-Test-Post Test Design approach. This type of research is the procedure of giving pre test before treatment and post test after treatment using a questionnaire instrument. The population in this study were 30 elderly people, while the study sample was 28 people. Result: the results of research conducted on July 19, 2019 to July 30, 2019, obtained data analysis with statistical tests using the Paired T-Test. The significance value or p value in the brain exercise function is 0,000 and the cognitive function is 0.002 with a significance level of 5% or α = 0.05. It is known that the correlation between before brain exercise and after brain exercise is 0.917. Conclusion: Because the significance value or p value α α = 0.05, H0 is rejected and H1 is accepted, which means there is an effectiveness of brain exercise for improving cognitive function in the elderly in Tegalan Village, Kandat District, Kediri Regency